Subjectivity Production of a Day-hospital Users: an sociopoetic experience - Lia Carneiro Silveira; Violante Augusta Batista Braga; Sandra Haydée Petit (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
We present part of a research developed with users of a mental health day-hospital of Fortaleza, Ceará with the objective of knowing the possibilities of subjectivity production for the person that lives the mental suffering in the current historical context. We used the sociopoética method that made possible, through the accomplishment of workshops, the approach of creativity and the sensibility aspects. The results show the concepts produced by the group and how this production provided the construction of new subjectivation spaces. We concluded making some considerations on the importance of establishing new possibilities to notice and to act towards the experience of madness.